Intima-media thickness in adolescents and young people - O. A. Kislyak; G. I. Storozhakov; E. V. Petrova; A. M. Kopelev; O. N. Tsareva; L. S. Potapova (Российский кардиологический журнал)
The study is devoted to high-definition ultrasound assessment of intima-media thickness (IMT), for identifying anatomic atherosclerosis manifestation in adolescents and young people. In total, 65patients (10 females and 46 males) were examined. Analyzing the influence of various cardiovascular risk factors on common carotid and femoral artery IMT, the authors demonstrated that these factors were associated with increased IMT, especially for common carotid artery, as early as in adolescence. IMT was significantly greater in adolescents and young people with stable hypertension, obesity, or metabolic disturbances typical for metabolic syndrome, than in healthy participants.